2015
DOI: 10.7314/apjcp.2015.16.10.4429
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge of Oral Cancer and Potentially Malignant Oral Disorders among Dental Patients in Far North Queensland, Australia

Abstract: Background: Public awareness/knowledge on oral and pharyngeal cancer (OPC), potentially malignant disorders (PMODs) and their risk factors is crucial for prevention and early detection of OPC and PMODs. Yet, there are no published data available on the awareness and knowledge of OPC and PMODs among people living in Far North Queensland, Australia. Materials and Methods: This study was conducted as a cross sectional survey. A self-administered questionnaire was designed and consisted of relevant questions to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
64
3
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 24 publications
14
64
3
10
Order By: Relevance
“…Disappointingly, only one fifth of subjects in this study knew about oral cancer from their dentists. This finding is in agreement with several awareness surveys that reported that the role played by dentists in educating their patients is secondary [16,19,21,22,26]. Limited patient attendance or accessibility to dental care personnel and deficiencies in knowledge among dental professional may explain why dentists are playing a lesser influential role than mass media in conveying oral cancer awareness among the public.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Disappointingly, only one fifth of subjects in this study knew about oral cancer from their dentists. This finding is in agreement with several awareness surveys that reported that the role played by dentists in educating their patients is secondary [16,19,21,22,26]. Limited patient attendance or accessibility to dental care personnel and deficiencies in knowledge among dental professional may explain why dentists are playing a lesser influential role than mass media in conveying oral cancer awareness among the public.…”
Section: Discussionsupporting
confidence: 90%
“…Although this rate of awareness is slightly higher than that reported among comparable hospital-based populations in Australia (52.3) [21], Jordan (45.6) [16], and the UK (56 %) [22], this figure is much lower than that reported in India (91.2) [20], Sri Lanka (95) [23], Yemen (71.5) [19], and the USA (84 %) [24]. Notably, higher levels of oral awareness have been reported from countries with a known high prevalence of oral cancer such as India and Sri Lanka.…”
Section: Discussioncontrasting
confidence: 68%
“…The awareness of other risk factors like poor oral hygiene, actinic radiation, viral infections and micronutrient deficiency was very low. Formosa et al (21) have reported that 92% of their study respondents agreed or strongly agreed that smoking is a strong risk factor for oral cancer, followed by tobacco chewing (84%), tobacco chewing with areca nut (68%), chewing areca nut alone (51%) and exposure to actinic radiation (71%) as risk factors. However, the results for alcohol intake, age, and HPV infection were found to be relatively poor with proportions 33%, 34%, and 23% respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Very few studies have investigated the awareness of individuals regarding OPMD (2,(19)(20)(21). A small number of studies have been dedicated to high risk patients, tobacco and alcohol users, but have been mainly limited to oral cancer awareness (9,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was divided into three parts: part A assessed the awareness of oral cancer, part B assessed the knowledge of signs and symptoms of oral cancer and part C assessed the respondents' knowledge of risk factors. This study differentiated between awareness and knowledge, based on the questionnaire by Agrawal et al (10) and Formosa et al (11). The response choices for each of the questions were categorised as 'incorrect', 'don't know' and 'correct'.…”
Section: Introductionmentioning
confidence: 99%